HIV/AIDS Awareness, Attitude and Perception among School, College Students and Hospital Workers - B, Premkumar; T, Gayathri; S, Ravichandran (Indian Journal of Pharmacy Practice)
Objective: To find out the level of awareness, attitude and perceptions of HIV/AIDS among School students, Pharmacy college students and hospital workers. Setting: PSG Sarvajana Higher Secondary School, PSG College of Pharmacy and PSG Hospital. Study design: Class XI and Class XII School students, III year and Final year Bachelor of Pharmacy Students and third grade hospital workers. Participants: 98 School students, 92 College students and 77 hospital workers participated in the study. Statistical analysis: Percentage and Chi-Square for comparison between the groups. Results: The awareness of Pharmacy college students was higher than School students. School students had better knowledge than hospital workers. Conclusion: Education has an impact on awareness and effective program design for each group could improve the understanding and behavior of the study population regarding HIV/AIDS.
Keywords: AIDS; Awareness; College; HIV; Hospital workers; School students